Does the quality of integrated reporting differ across different industries? a comparative study of mining and financial sectors - Ravid Nur Wahid; Erfan Muhammad; Tito IM. Rahman Hakim; Frida Fanani Rohma; Reddy Setiawan (Universitas Muhammadiyah Malang, 2024)
Purpose: This research was conducted to test the influence of the board of directors and audit committee on IR quality and to compare IR quality in mining and financial sector companies.Methodology/approach: The research uses secondary data from the annual reports of mining and financial sector companies listed on the IDX for 2019-2022. Stata 17 and SPSS 26 were used to analyze the data and test the hypotheses. Findings: The empirical findings showed that the board of directors in mining companies did not affect IR quality. Meanwhile, different results were found in financial companies where the board of directors significantly affected IR quality. The audit committee did not significantly affect the quality of IR in mining and financial companies. Furthermore, it was found that there were significant differences between IR quality in mining and financial sector companies. Practical and Theoretical Contribution/Originality: This study's findings verify the IR quality discrepancy between different sectors. Government and policymakers must reevaluate the regulations regarding the number of boards of directors and audit committees to ensure the mentioned entity contributes to improving IR quality. Research Limitation: Although this study provides empirical evidence regarding the difference in IR quality between the mining and financial sectors, it fails to address which sector has better IR quality.